Zygomycosis in Two Hematologic Cases - M. T. García-Romero; J. García-Méndez; R. Arenas; T. Ferrari-Carballo; J. Chanona-Vilchis; E. Cervera-Ceballos (Case Reports in Infectious Diseases)
Zygomycosis are invasive mould infections, rarely diagnosed in hematologic patients. Most of the cases published are in patients with prolonged neutropenia, along with other risk factors such as the use of prior broad-spectrum antibiotics (including new antifungal agents, such as voriconazole), diabetes mellitus (with or without ketoacidosis), malnutrition, iron overload (with or without the use of deferoxamine). These infections have poor prognosis due to the involvement of vital anatomic structures and late diagnosis. Until recent years, the treatment was based on high doses of amphotericin B plus surgical debridement. Here we present two patients with hematologic diseases (one with leukemia, the second with aplastic anemia) with an impaired immune system and the diagnosis of zygomycosis. The survival of one of them was mainly due to early diagnosis and surgical debridement; unfortunately the second was misdiagnosed as an extensive ecchymosis due to thrombocytopenia and died with CNS involvement.